1983
DOI: 10.2134/jeq1983.00472425001200020002x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Elements in Soils Under Cattle Pens

Abstract: In cattle feedlots, the manure builds up and to some extent becomes incorporated into the soil profile through downward leaching and the stirring action created by the cattle. The object of this study was to measure the extent of build‐up of certain chemical elements resulting from the cattle wastes within the soil profile (Felda fine sand) in a cattle feedlot after 10 and 15 y. Soil samples were taken at 15‐cm increments from the soil surface to a depth of 137‐cm. Results indicated most of the increase of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Major ions in manure include N, K, Ca, Cl, P, Mg, and Na (American Society of Agricultural Engineers, 2000). Dantzman et al (1983) found that Mg 2+ , Ca 2+ , Mn 2+ , soluble salts, and Fe 2+ all increased in the top 1.5 m of the soil after feedlot pens had been in place for 15 yr.…”
Section: Resultsmentioning
confidence: 91%
“…Major ions in manure include N, K, Ca, Cl, P, Mg, and Na (American Society of Agricultural Engineers, 2000). Dantzman et al (1983) found that Mg 2+ , Ca 2+ , Mn 2+ , soluble salts, and Fe 2+ all increased in the top 1.5 m of the soil after feedlot pens had been in place for 15 yr.…”
Section: Resultsmentioning
confidence: 91%
“…Studies of physical and chemical properties of feedlot pen soils with a focus on leaching have been conducted on single feedlots located on moderately coarse–textured (MC) (very fine sandy loam, fine sandy loam, sandy loam) and coarse‐textured (loamy sand, sand) soils (Campbell and Racz, 1975; Dantzman et al, 1983; Southcott and Lott, 1997; McCullough et al, 2001). Most of these studies reported little evidence for leaching below feedlot pens.…”
mentioning
confidence: 99%
“…The containers were left in the incubator for 18 weeks (126 days), i.e. the average maximum clean-out period for manure on pens in Queensland (Skerman 2004) and representative of typical clean-out periods for pens in the USA (Dantzman et al 1983). The experiment represents a decay simulation for pendeposited manure with the aim to estimate the impact of decay on manure C and Si concentrations.…”
Section: Fresh Manure Decay Experimentsmentioning
confidence: 99%
“…No practical methods exist for quantifying base material/manure mixing on pen surfaces. Uncertainty regarding the extent of base material mixing with manure causes mass balance problems in fields such as nutrient and carbon (C) budgeting (Dantzman et al 1983;Eghball et al 1997), and greenhouse gas emission measurement where emissions from pad manure are often reported on a manure weight basis without necessarily accounting for the amount of soil/rock mixed in with it (Hao et al 2001;Pattey et al 2005). Indeed, the need for quantifying base material mixing with manure on feedlots has arisen in studies examining in situ soil profiles in feedlot pens (Mielke et al 1974;Dantzman et al 1983;Berry and Miller 2005;García et al 2012) as well as investigations into characterising manure hauled from feedlot pens (Larney et al 2000;Rogge et al 2006).…”
Section: Introductionmentioning
confidence: 99%